Measuring the impact with the social return on investment: the case of the social innovation HUB - Carvalho, Isabel Maria Pimentel dos Santos Lopo de (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Economics from the NOVA – School of Business and Economics